Contentious buildings: The struggle against eviction in NYC’s Lower East Side - Accornero, G. (Current Sociology, 2022)
The article focuses on the mobilization carried out by tenants living in a rent-stabilized building in NYC’s Lower East Side. Their action was a central part of a large and successful struggle against the landlord, blocking his continuous attempts at eviction. The main research question is: what are the reasons of the success of this action? In other words: what has tipped the balance in favor of the tenants in a conflict in which the landlord clearly had stronger economic, political and power resources? The article argues that this success was highly based on the intersection of three main elements: the specific resources of the tenants, the organizational resources of the territory and the institutional and legal configurations. Moreover, the study considers these three levels closely interconnected and mutually influencing each other. Based on the direct observation of the mobilization, on semi-structured interviews and on biographical sources, the article aims to contribute to the understanding of the multifaceted dimensions of the fight against evictions. The article also aims to contribute, theoretically and methodologically, to a relational and interactionist approach both for the study of social movements and of gentrification and to strength the dialogue between the two fields.